The use of authentic video materials in language teaching - Elena V. Revina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with using of authentic materials in the classroom which are necessitated by modern society. First, the article provides a brief overview of how authenticity is defined by other authors. Authenticity of materials as a tool for raising cultural awareness is discussed. Authentic materials give students the possibility to come in contact with real language and content rather than form and they feel that they are learning the target language as it is used outside the classroom. It makes possible to combine educational situation with real communications. The author points out the motivation of learners. Then it goes on to inform important factors in choosing authentic video material. The problem of rational use of authentic video is discussed. This paper aims at looking into the ways in which teachers of foreign languages can incorporate authentic video materials in their lessons. The methods of using authentic films are presented. The problem of rational use of authentic video is given in the program design for the use of authentic video on the lessons for German language.